Morphological changes of the calamus of growing remiges feathers in pigeons (2018)
Feathers have been studied in processes of cellular differentiation and morphogenesis; however, only few histological studies in adult animals describe the maturation of the cellular components sequentially. Therefore, the objective of this work was to describe the histological characteristics, covering the cellular elements and their anatomical relationships. Pigeon feathers were withdrawn to induce regeneration, and samples were taken at different times: 8 (sprout time), 13, 18, 23, and 28 days. We prepared histological cuts using different staining techniques. We demonstrated the presence of a very marked ramogenic zone that tends to diminish from day 8 to 28. In the barb ridge, we observed the barb, barbule, and axial plate cells, with the marginal plate delimiting each barb ridge. The cellular characteristics varied according to the ridges region, showing in the marginal plate transitions from squamous to cuboidal and back to squamous cells; and, in the barbular plate, from cuboidal to columnar and then to fusiform cells. Obscure cells from the ramogenic zone were identified as cells derived from the dermal papilla based on their staining. In conclusion, we characterized the histology of the calamus and, for the first time, described the different growth stages sequentially.